The concepts «politics», «politician» in the Anglo-Indian mass media discourse - Alexeyev, Alexander B. (Journal of the Belarusian State University. Journalism, 2022)
The article is dedicated to the study of concepts «politics», «politician» based on the material of the Anglo-Indian mass media discourse. All in all, 10 news texts have been analysed. It has been found out that the basic meanings of the concepts remain unchanged but the connotative and evaluative aspects of the meaning are transformed. Thus, concepts «politics», «politician» are often imbued with negative characteristics that are not traditionally inherent to them. The discreditation and critics of everything linked to politics is connected with the actual political events and serve the lingvopragmatic purpose of the accusation of those countries that, in the opinion of the journalists, are not friendly to India. Simultaneously, the stereotypic attitude to the analysed concepts helps the mass media to explain difficult political processes. Even if this explanation is simplified, it is understandable for the addressee.
Keywords: politics; politician; concept; mass media; mass media discourse; India